Phenological Aspect of Madhaulia Forest, Gorakhpur - Ansari, A. A. (Indian Forester, 1989)
The phenological behaviours of 726 angiospermic species recorded from Madhaulia forest hale been studied. An attempt has been made to study the influence of two major climatic factors viz. rainfall and temperature on flowering periods of woody and herbaceous plants. The correlation indicates that flowering period of woody plants is maximum during March-April, while herbaceous plants showed maximum flowering during July-September.